Nujno dedovanje (in z njim povezani instituti) v slovenski sodni praksi - Pavlin, Sabina (Pravni letopis, 2025)
The article analyses several important judicial decisions of the Supreme Court of the Republic of Slovenia (SCRS) and the Constitutional Court of the Republic of Slovenia issued over past fifteen years on compulsory succession and related institutes and, in the author’s opinion, have significantly contributed to the development of the law in this area. It focuses on the subject of gifts which, under the law, are to be added to the net value of the estate for the purpose of determining the accrued value of the estate, which is the basis for the determination of the necessary shares, with particular emphasis on the judicial decisions in which the SCRS has considered the (non)payment of lifetime maintenance and survivorship contracts, as well as recent judicial decisions on the institution of the exclusion of a decedent’s estate in favour of their descendants under the Article 32 of the Succession Act, which also significantly impacts the calculation of the forced share. The article also draws attention to the incorrect admission of the nullity sanction for the deprivation of the forced share in contemporary Slovenian case law and the unnecessary introduction of the problem of the constitutionality of the right to the forced share into the decisions of the SCRS, which deal (only) with the issue of the (non)payment of lifetime maintenance or survivorship contracts. Finally, it analyses two recent court decisions concerning incapacity to inherit and on the disinheritance of forced heirs.
Keywords: case law; necessary succession; novejša sodna praksa Vrhovnega in Ustavnega sodišča Republike Slovenije; nujno dedovanje; recent case law of the Supreme Court and the Constitutional Court of the Republic of Slovenia; sodna praksa